2013
DOI: 10.1159/000353261
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiorenal Syndrome: What the Cardiologist Needs to Know

Abstract: Interactions between the heart and the kidneys are increasingly acknowledged among both cardiologists and nephrologists. The term cardiorenal syndrome now applies to the bidirectional nature of how disease in one organ system affects the function of the other organ system. Cardiovascular disease is a major threat to patients with chronic kidney disease, while renal dysfunction is prevalent in patients with cardiac disease and is a significant predictor of prognosis in cardiac patients. Still, renal patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 100 publications
1
14
0
4
Order By: Relevance
“…The reports vary significantly in different datasets, depending on the specific criteria used, but the figures are similar in patients with HFrEF and HFpEF. The interdependence of heart and kidney dysfunction is captured by the recently described “cardiorenal syndrome” (7,80). Renal dysfunction may worsen HF through multiple mechanisms, including increased sodium and fluid retention, anemia, inflammation, and uremic toxins, as well as RAAS and sympathetic activation.…”
Section: Comorbidities In Hfref Versus Hfpef Patients: Prevalence Oumentioning
confidence: 99%
“…The reports vary significantly in different datasets, depending on the specific criteria used, but the figures are similar in patients with HFrEF and HFpEF. The interdependence of heart and kidney dysfunction is captured by the recently described “cardiorenal syndrome” (7,80). Renal dysfunction may worsen HF through multiple mechanisms, including increased sodium and fluid retention, anemia, inflammation, and uremic toxins, as well as RAAS and sympathetic activation.…”
Section: Comorbidities In Hfref Versus Hfpef Patients: Prevalence Oumentioning
confidence: 99%
“…Using ESRD as the primary outcome, our study showed that the addition of ACEI/ARB to pentoxifylline achieved no further benefits in ESRD risk reduction in predialysis stage 5 CKD, and, moreover, that pentoxifylline alone conferred a lower risk of initiation of long‐term dialysis than ACEI/ARB monotherapy. Consistent with clinical practice and especially in patients with cardiorenal syndrome, RAAS blockade for CKD is not always associated with an improvement in renal function . Although most patients have an attenuating reduction after the initial functional drop in GFR, a minority of patients have a conspicuous decrease in GFR or hyperkalemia that can often be ameliorated by withholding ACEI/ARB therapy.…”
Section: Discussionmentioning
confidence: 96%
“…In 2008, the CRS was subdivided into five types (Ronco et al, 2008;Ronco et al, 2010;Waldum & Os, 2013).…”
Section: Examples Of Vasodilators Involved In Splanchnic Dilationmentioning
confidence: 99%
“…However, during an incident of total loss of kidney function, the fluid retention is caused by the loss of kidney function itself; in all other cases of CRS, type 3 and 4 fluid retention is most likely caused by interaction between changes in vasculature, pharmacodynamics, mineral and vitamin metabolism, as well as production of inflammatory cytokines (Waldum & Os, 2013;Clementi et al, 2015). However, during an incident of total loss of kidney function, the fluid retention is caused by the loss of kidney function itself; in all other cases of CRS, type 3 and 4 fluid retention is most likely caused by interaction between changes in vasculature, pharmacodynamics, mineral and vitamin metabolism, as well as production of inflammatory cytokines (Waldum & Os, 2013;Clementi et al, 2015).…”
Section: Fluid Retention In Crsmentioning
confidence: 99%